Ful Medames - Heine, Peter; Harris, Russell; Perry, Charles; Kurtze, Eva (Petits Propos Culinaires, 1993)
The Query from John Thorne in PPC 41 attracted many responses, which we thought suitable for presentation together as a collection, in what might be termed a micro-symposium on this highly specific and interesting subject. John Thorne tells us that his editor had seen a connection with an Arabic word hamam, meaning pigeon; the thought is that the beans used are ful hamam, meaning literally pigeon peas, and that there is a pun involved since there is another word, hamam, meaning a (hot) bath and conveying the idea of something being heated. However, we are told by others that there is no word hamam meaning pigeon! Patience Gray has written to say that she is not satisfied with what has been said so far about the identity of the beans which are used: how, precisely, would a botanist or horticulturist refer to them? Further contributions welcome.